Patellofemoral and tibiofemoral forces in cyclists and triathletes: effects of saddle height - Bini, R. R. (Journal of Science and Cycling, 2012)
High compressive load applied to the patellofemoral joint at great knee flexion angle (e.g. >60º of flexion), as usually observed in cycling may provide a link between body position on the bicycle and knee joint forces. The aim of the present study was to compare knee joint forces in different saddle heights. Right pedal force and lower limb kinematics were collected for 24 competitive cyclists and triathletes at self-selected preferred, high (-10º of knee flexion angle from preferred), low (+10º of knee flexion angle from preferred) and optimal (25º of knee flexion angle) saddle heights in submaximal pedalling cadence and workload trials (3.45 ± 0.6 W/kg, 90 ± 2 rpm and 163 ± 33 J). Patellofemoral compressive and tibiofemoral anterior-posterior and compressive force were computed by inverse dynamics and compared for different saddle heights via effect sizes. Patellofemoral compressive force (5-13%) and tibiofemoral compressive force (1-7%) were not substantially affected by changes in saddle height. Tibiofemoral anterior shear force decreased at low saddle heights (4-6% of the preferred height) compared to optimal (35%) and high saddle heights (53%). Greater knee flexion angles were observed for lower saddle heights (8-34%). Knee flexion angle was significantly affected by changes in saddle height, which may indicate that using joint kinematics to assess saddle height effects may be useful to anticipate overload in knee joint.